2013
DOI: 10.1128/aem.02833-12
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclovorans algicola gen. nov., sp. nov., an Aromatic-Hydrocarbon-Degrading Marine Bacterium Found Associated with Laboratory Cultures of Marine Phytoplankton

Abstract: f A strictly aerobic, halotolerant, rod-shaped bacterium, designated strain TG408, was isolated from a laboratory culture of the marine diatom Skeletonema costatum (CCAP1077/1C) by enrichment with polycyclic aromatic hydrocarbons (PAHs) as the sole carbon source. 16S rRNA gene sequence analysis placed this organism within the order Xanthomonadales of the class Gammaproteobacteria. Its closest relatives included representatives of the Hydrocarboniphaga-Nevskia-Sinobacter clade (<92% sequence similarity) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 58 publications
3
60
0
Order By: Relevance
“…Whether through biogenic synthesis or adsorption from the surrounding seawater, the phycosphere of marine eukaryotic phytoplankton may be regarded as a hot spot to which hydrocarbon-degrading bacteria are associated. This concept is supported by our recent discovery of several novel hydrocarbon-degrading bacteria in laboratory cultures of marine phytoplankton (6)(7)(8). Notably, these bacteria conferred the ability to utilize PAHs as sole sources of carbon and energy and exhibited a nutritional preference for hy- drocarbons over other carbon substrates.…”
Section: Physiology and Ecology To Our Knowledge Strain Tg409supporting
confidence: 49%
See 1 more Smart Citation
“…Whether through biogenic synthesis or adsorption from the surrounding seawater, the phycosphere of marine eukaryotic phytoplankton may be regarded as a hot spot to which hydrocarbon-degrading bacteria are associated. This concept is supported by our recent discovery of several novel hydrocarbon-degrading bacteria in laboratory cultures of marine phytoplankton (6)(7)(8). Notably, these bacteria conferred the ability to utilize PAHs as sole sources of carbon and energy and exhibited a nutritional preference for hy- drocarbons over other carbon substrates.…”
Section: Physiology and Ecology To Our Knowledge Strain Tg409supporting
confidence: 49%
“…T (6) and Porticoccus hydrocarbonoclasticus strain MCTG13d T (7) were both isolated from the marine dinoflagellate Lingulodinium polyedrum CCAP1121/2, whereas Polycyclovorans algicola strain TG408 T was isolated from the marine diatom Skeletonema costatum CCAP1077/1C (8). These organisms all represent novel "specialist" hydrocarbon degraders; i.e., they exhibit an almost exclusive requirement for hydrocarbons as their preferred carbon and energy source.…”
mentioning
confidence: 99%
“…It was also suggested that Xanthomonadales and Pseudomonadales in the soil exhibited weaker BPA degrading activity than strain AO1. Indeed, some bacter i a l s t r a i n s , b e l o n g i n g t o X a n t h o m o n a d a l e s , Pseudomonadales, Burkholderiales, Caulobacterales and Enterobacteriaceae, have already been reported as degradative bacterium against aromatic compounds, phenolic compounds or polycyclic aromatic hydrocarbons Ammar et al, 2005Chatterjee and Bourquin, 1987Gutierrez et al, 2013Haritash and Kaushik, 2009O Sullivan and Mahenthiralingam, 2005 Furthermore, our results indicated that BPA purification by strain AO1 and the soil bacteria improved or re s t o re d t h e b a c t e r i a l d i v e r s i t y, f o r e x a m p l e , Be taproteobacteria, except Burkholderiales, were reduced in BPA polluted soil after 7 days without strain AO1 but were restored at day 50, and unclassified bacteria were also reduced after 7 days in the BPA polluted soil with strain AO1 but were restored at day 14 FIG.5 . It was also observed that strain AO1 was only detectable in the BPA polluted soil but not in the purified soil, based upon the Southern hybridization method using the bisdB gene probe data not shown , which encoded a BPA degradation enzyme in strain AO1 Sasaki et al, 2008 , suggesting that strain AO1 might not lead to a heavy burden in the soil environment.…”
Section: U R K H O L D E R I a L E S 4 P S E U D O M O N A D A L E mentioning
confidence: 99%
“…This study was supported in part by the MEXT-Supported Programs for the Strategic Research Foundation at Private University 2008-2012and 2013-2018 …”
Section: Acknowledgementsmentioning
confidence: 99%
“…To date, numerous novel bacteria have been isolated from marine microalgae environments (Nedashkovskaya et al, 2003;Gutierrez et al, 2012Gutierrez et al, , 2013Wang et al, 2013). In this study, a polyphasic taxonomic analysis was performed on strain GYP-24 T , which was isolated from the culture broth of a marine microalga, Picochlorum sp.…”
mentioning
confidence: 99%